Modbus Protocol as Gateway between different Fieldbus devices: a Didactic Approach - Cordeiro, Armando (2017)
This paper is dedicated to improve the skills of Electric Engineering students about Industrial Automation. This is done creating a set of practical exercises in the laboratory that allow students to interact with didactic and industrial equipment understanding the compatibility problems and give students the tools, the knowledge and even some creative freedom to solve problems that happens in real situations. In this case, it was focuses in the interconnection of equipment from different manufacturers using the Modbus protocol. To allow to the students this practical study, it was developed a solution with a Modbus RTU protocol directly implemented in program memory of both S7-200 (using the Freeport configuration mode) and S7- 300 PLCs. The solution allows a gateway between Modbus-TCP (over a Master TSX PLC from Schneider-Electric) and Profibus-DP (over a Master S7-300 PLC from Siemens).